Molecular Links Between Alzheimer's Disease and Gastrointestinal Microbiota: Emphasis on Helicobacter pylori Infection Involvement - Katsinelos, Taxiarchis; Doulberis, Michael; Polyzos, Stergios A; Papaefthymiou, Apostolis; Katsinelos, Panagiotis; Kountouras, Jannis (Current Molecular Medicine, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease and the main form of dementia, characterized by progressive cognitive decline and detrimental consequences in both personal-family and global level. Within this narrative review, we provide recent molecular aspects of Tau, a microtubule AD-associated protein, as well as amyloid beta, involved in AD pathophysiology. Moreover, we provide additional emerging data from basic research as well as clinical studies indicating an implicating role of gastrointestinal microbiota (GI-M), including Helicobacter pylori infection (Hp-I), in AD pathophysiology. Likewise, we identified through a molecular prism the current evidence of AD pathogenesis as well as its linkage with GI-M and emphasizing the role of Hp-I. All in all, additional large-scale studies are required for the further clarification of AD pathophysiology and its connection with GI-M and Hp-I, so as novel therapies on molecular basis become available.
Keywords: tauopathies